User Experience Testing on JoinGeek Admin using a User Experience Questionnaire and Usability Testing - Kusuma Dewi, Fatimah Azzahra (Sistemasi: Jurnal Sistem Informasi, 2024)
Job vacancy portals are becoming increasingly popular as a primary tool for job searching. As a result, developing and improving the quality of job vacancy portals is a suitable response to these changes. As job vacancy portals evolve, it is also vital to pay attention to adjustments to the dashboard that HR uses to process applications. As a technology firm, Geekgarden understands the importance of this development and is committed to improving JoinGeek Admin, their HR dashboard, to keep it relevant to this issue. This study compares the user experience on JoinGeek Admin before and after the redesign to determine the success of the new design. The methods employed are the User Experience Questionnaire (UEQ) and usability testing. The UEQ technique measures six dimensions: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. The evaluation results reveal considerable improvements in all areas of the system before and after the redesign, which increase in each dimension: attractiveness (+2.166), perspicuity (+1.666), efficiency (+2.416), dependability (+2), stimulation (+2.5), and novelty (+0.834). Usability testing evaluates the system after redesign in terms of success rate, efficiency, and error rate. The test results reveal a success rate of 94%, an efficiency of 92.5%, and a low error rate of 3.8%. Thus, the evaluation findings show that the JoinGeek Admin redesign was successful in improving the user experience in all areas.